SPIRITUALITY AND IRRATIONAL BELIEFS OF MOVEMENT ACTIVITIES IN SLOVAKS AND CZECHS - Cergetova, Ivana Tomanova; Maturkanič, Patrik; Hlad, Ľubomir; BIRYUKOVA, YULIA NICKOLAEVNA; Martin, Jose Garcia (Journal of Education Culture and Society, 2021)
Aim. The present study is focused on exploring of the relationship between spirituality and irrational beliefs particularly in relation to movement activities in Slovakia and Czechia, i.e., helplessness, idealisation, perfectionism, external vulnerability, and negative expectation. Concept. Our research has been focused on the investigation, comparison, and correlation between the level of spirituality and irrational beliefs depending on the frequency of sport activities. Method. The research sample (N = 469) consisted of Slovak and Czech health population aged 18-70 (M = 41.97, SD = 13.14), of which 42.2% were men (N = 198) and 57.8% were women (N = 271). The level of spirituality was identified by means of the Expressions of Spiritual Inventory-Revised – ESI-R (MacDonald, 2000). The irrational beliefs were measured using the Scale of Irrational Beliefs (Kondáš & Kordáčová, 2000). Results. Research results confirmed the differences between the variables of spirituality and irrational beliefs based on the frequency of sports activities. Also, we confirmed the hypothesis of negative correlation between spirituality and irrational beliefs. Conclusion. In our study, we focused on the correlations between irrational beliefs and spirituality in group of Slovak and Czech population. Based on our results we can draw several conclusions. Research results confirmed the differences between the variables of spirituality and irrational beliefs based on frequency of sports activities.